Legal Philosophy Values in the Law Formation in Indonesia - Agustina, Ria; Anas, Kamal; Jalaluddin, Jalaluddin; Fikri, Ahmad Ma’mun (LEGAL BRIEF, 2025)
The most significant influence on the development of Indonesian law is legal philosophy. The term "Pancasila" refers to the entirety of regulations and laws, beginning with our constitution. All regulations that are not based on our constitution must establish Pancasila as the basis and foundation of the law. Indonesia's legal framework is known as Pancasila. Consequently, Pancasila is recognized as both a philosophy and a written law in Indonesia that encompasses living law. The issue is the extent to which legal philosophy influences the development of the legal system in Indonesia. Certainly, it is crucial to address this issue. The legal method was implemented by the authors to evaluate this issue with normative law. The authors' methodology was derived from numerous books that address comparable issues. The results of this research show that Legal philosophy is a critical component of Indonesian law, serving as both a guide for its development and a necessity. Legal philosophy contributes to the elucidation of the philosophical foundation of legal values, capable of achieving the ideals of justice and order in society in accordance with the reality of the applicable law